Immature reticulocyte fraction and erythrocyte indices in children with homozygous sickle cell disease during the interictal phase: A cross-sectional study in Lubumbashi. - Arold Fazili; Priscille Lushimba Samukini; Adonis Kalume; Armand Abasi; Jean Paul Nbolua Koto-Te-Nyiwa (Student's Journal of Health Research Africa, 2026)
Introduction: Homozygous sickle cell disease (SS) is a hemoglobinopathy characterized by chronic hemolytic anemia and vaso -occlusive crises. In Lubumbashi (DRC), routine laboratory evaluation is often limited to a complete blood count, neglecting advanced reticulocyte parameters. This study aims to evaluate the profile of the immature reticulocyte fraction (IRF) and erythrocyte constants in children with SS sickle cell disease during the intercritical phase. Methods: A descriptive cross-sectional study was conducted on 49 children with SS sickle cell disease, aged 1 to 12 years, followed at the DeeServices Medical Laboratory. Hematological parameters, including hemoglobin, mean corpuscular volume (MCV), and IRF (sum of medium and high fluorescence fractions), were measured using the URIT 5160 analyzer. Statistical analysis was based on Spearman's rank correlation coefficient to assess the relationships between variables, in accordance with the principles of the Declaration of Helsinki. Results: The cohort presented with severe anemia, with a mean hemoglobin concentration of 7.33 g/ dL and impaired erythrocyte indices. The median IRF was 23.30%, reflecting significant reticulocyte stress and sustained compensatory erythropoietic activity. A positive and highly significant correlation ( rho = 0.923, p < 0.001 ) was found between IRF and the absolute reticulocyte count. Conclusion: The intercritical phase in children with sickle cell disease (SS) does not correspond to a state of biological rest, but rather to active bone marrow regeneration. The IRF (erythropoietic response index) proves to be a relevant indicator for documenting the erythropoietic response in a cross-sectional setting. Recommendation: It is recommended that hospital laboratories in Haut-Katanga routinely integrate automated hematological analyzers capable of measuring IRF alongside absolute reticulocyte counts to accurately assess bone marrow regenerative activity during the interictal phase of pediatric sickle cell disease.